The comparison of two programmes to measure color difference (ΔE) from tooth sample photo - Annisa, Mutiara; Harsini, Harsini; Nuryanti, Archadian (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Color evaluation is crucial to evaluate a material’s quality. One alternative method for evaluating material’s color is using photographs analysed by software. This research evaluates the use of digital imaging and software (ImageJ and Photoshop) to obtain color differences of tooth sample in-vitro. Method: The sample used is bovine teeth that were given tea-staining and brushing treatment using five tested toothpastes. Sample’s photographs for each toothpaste’s group (n=4) were taken before and after experiment. DLSR Nikon D90 was used with digital CCD censor, macro lens 105mm, manual setting (ISO 200, F-Stop 5, Shutter Speed 1/400) with distance to sample of 25cm. Sample was positioned in foldable mini-studio-box (24.5x24.5x22.5cm) with LED-lighting (6500-7000 color temperature). The photographs were taken in close room at 11.00am. Two software were used to obtain the color value from pre- and post-experimental photographs of the sample at the middle-third of the sample using CIE-Lab (Commision Internacional de l’Eclairage L*a*b) color system. The resulted color difference (ΔE) value of sample from the two-software were compared using independent T-test and evaluate the measurement accuracy using Pearson’s correlation (α=0.05). Result: ImageJ and Photoshop analyses of the sample photographs yield comparable ΔE values, as determined by an independent T-test (p=0.893). The Pearson correlation test reveals a positive correlation (R=0.904) between the two software. Conclusion: The use of digital photography and software to obtain ΔE values are accurate, representative, and recommended when taking into account the controlled procedure of photographing the sample and analysing the sample's color value.